A philosophical perspective on contemporary evolutionary economics - Geoffrey M. Hodgson (Max Planck Institute of Economics, 2010)
There has been a remarkable growth in evolutionary economics since the 1980s. But despite this outward success there has been inner disagreement on fundamental issues including the building blocks of evolutionary theory and the very meaning of evolution itself. This essay provides a philosophical perspective on both the defining agreements and ongoing disputes within evolutionary economics. Its primary emphasis is on ontology. It shows that some major disputes derive not from incompatible propositions but the choice of different levels of analysis. A route toward reconciliation of different viewpoints is thus exposed.
Keywords: 330